S100A1 gene therapy in small and large animals - Most, Patrick; Raake, Philip; Weber, Christophe; Katus, Hugo; Pleger, Sven Torsten (Calcium-binding proteins and RAGE, 2013)
Myocardial in vivo gene delivery is a valuable technique to investigate the relevance of a protein of interest on cardiac contractile function, hypertrophy, and energy state in healthy animals as well as in a variety of models of cardiovascular disease. Rodent models are used to screen effects and to investigate molecular mechanisms, while large animal models, more closely reflecting human anatomy, physiology, and function, are inevitable for translational therapeutic approaches. The gene of interest, whose expression is driven by a non-cardioselective or cardioselective promotor is cloned into a viral vector. This vehicle is then delivered using an appropriate administration route to target the heart and to achieve efficient protein expression in myocardium.Here we describe myocardial gene therapy in small and large animal models of postischemic heart failure used to reveal the positive inotrope, antihypertrophic, and pro-energetic action of the small calcium sensor protein S100A1.
First online: 04 November 2012
Gesehen am 20.07.2021